Sejarah Perkembangan Undang-Undang Kesehatan Jiwa Dan Pasung Terhadap Orang Dengan Gangguan Jiwa Di Indonesia - Lyani, Muhammad Rivaldo; Fitriasih, Surastini (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2024)
The act of shackling is mostly carried out by their own family on the grounds that they are afraid of hurting local residents or their family. This article discusses the history of the development of the Mental Health Law and the Development of Shackling of People with Mental Disorders in Indonesia. This study uses a normative legal problem approach. The type of data used is secondary data obtained through literature studies. Data analysis was carried out using a qualitative descriptive method. The conclusion is that the Development of the Law on Mental Health continues to develop with the hope of continuing to protect and provide services to patients with mental disorders, as well as improving legal services for perpetrators of shackling in accordance with Article 86 of Law Number 18 of 2014 with the threat of criminal penalties for perpetrators of shackling People with Mental Disorders. In its development, the regulations governing shackling have also developed